PENGUKURAN DIMENSI LUAR, DALAM SERTA TEBAL RELATIF DIVAIS ELEKTRONIK MEMORI USB MENGGUNAKAN CITRA RADIOGRAFI - Harnawan, Ade Agung; Oktivasari, Prihatin (Jurnal Fisika FLUX, 2013)
ABSTRACT: Radiographic imaging has been done for profile aluminium witharrange in steps and 5 USB memory to measure the dimension inner and outerpart of 5 USB memory without destroying it. Based on this image, the functionof characterization for relative thickness of aluminiums profile with grayscalelevel is gained. With characteristic mentioned before the dimension and relativethickness of profile memory USB is determined. The result are the dimensionouter part of profile that consist of the length is 31â57 pixel, the width is 13â22pixel and the wide is 465â1197 pixel2, later the dimension inner part of profilethat consist of the length is 28â30 pixel, the width is 10â16 pixel and the wide is300â480 pixel2 and the last, the relative thickness of electronics device is rangefrom 3,36â7,62 mm.Keywords: radiographic imaging, dimension of USB memory, relativethickness, aluminium